The Influence of Family in Shaping the Political Culture of Society - Kisno Hadi (Journal Ilmu Sosial, Politik dan Pemerintahan, 2026)
This article aims to reveal the influence of the family in shaping the political culture of the Dayak community in Kurun Subdistrict, Gunung Mas Regency and as the challenges. Based on the author’s research conducted in 2025 using a qualitative descriptive method. This article will describes i.e. (1) the family functions as a medium of political socialization for children and other family members; and (2) the family provides political information to children and family members. Some obstacles to the family’s role in shaping political culture include: (1) limited knowledge and insight among children and family members; (2) the large number of political terms that are not understand by children and family members; (3) differences of opinion between parents and children; and (4) lest communication time between parents and children.